The homozygote p.V27I/p.E114G variant of GJB2 is a putative indicator of nonsyndromic hearing loss in Chinese infants. (May 2016) - Chen, Wen-xia; Huang, Yue; Yang, Xiao-lin; Duan, Bo; Lu, Ping; Wang, Yan; Xu, Zheng-min
Abstract: The gap junction β2 ( GJB2 ) gene is associated with more than half of the recessive forms of hereditary hearing loss (HHL). However, the correlation between p.V27I and p.E114G variants of GJB2 and hearing phenotype remains controversial. This study aimed to clarify possible roles of these variants in Chinese infants with nonsyndromic hearing loss (NSHL). Hearing and gene tests were conducted in 300 infants (aged 0–3 months) with NSHL and 484 normal infants (aged 0–3 months). The p.V27I and p.E114G variants appeared frequently in both NSHL patients and normal controls. The allele and haplotype frequencies of p.V27I and p.E114G in patients and controls were compared, but no significant difference was observed ( p = 0.44 and p = 0.26, respectively). Moreover, genotype frequencies of the p.V27I variant showed no significant difference between the two groups ( p = 0.66). Interestingly, more homozygote p.V27I/p.E114G subjects were found in NSHL infants than in controls (5/484 and 13/300, respectively), most of whom (61.54%) had mild or moderate hearing losses. Our results indicate that homozygote p.V27I/p.E114G is associated with mild and moderate HHL.